The impact of social security reform on occupational and retirement behavior : a quantitative assessment for Brazil - Parente, Rafael Machado (2016)
Population ageing is a problem that countries will have to cope with within a few years. How would changes in the social security system affect individual behaviour? We develop a multi-sectoral life-cycle model with both retirement and occupational choices to evaluate what are the macroeconomic impacts of social security reforms. We calibrate the model to match 2011 Brazilian economy and perform a counterfactual exercise of the long-run impacts of a recently adopted reform. In 2013, the Brazilian government approximated the two segregated social security schemes, imposing a ceiling on public pensions. In the benchmark equilibrium, our modelling economy is able to reproduce the early retirement claiming, the agents' stationary distribution among sectors, as well as the social security deficit and the public job application decision. In the counterfactual exercise, we find a significant reduction of 55% in the social security deficit, an increase of 1.94% in capital-to-output ratio, with both output and capital growing, a delay in retirement claims of public workers and a modification in the structure of agents applying to the public sector job.